2013
DOI: 10.1021/ie302975b
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations of a Packed Calcite Bed for Hardening Desalinated Water

Abstract: Desalinated water is poor in minerals, making it corrosive and unpalatable. A certain degree of remineralization is necessary in order to overcome these problems as well as to meet health requirements. A commonly used remineralization process is to pass desalinated water dosed with either CO2 or H2SO4 through a bed of limestone, reintroducing bicarbonate alkalinity and calcium hardness to the water. The paper presents cumulative experimental evidence confirming the reliability of the kinetic model developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…CaCO3 + CO2 + H2O → Ca 2+ + 2 HCO3 -(Eq. 1) Several researches have shown that calcite filtration is a reliable remineralization method as no continuous chemical addition is required and calcite is inexpensive, readily available, safe to handle and easy to store (Shemer et al, 2013, Van Der Laan. H., 2016.…”
Section: Introductionmentioning
confidence: 99%
“…CaCO3 + CO2 + H2O → Ca 2+ + 2 HCO3 -(Eq. 1) Several researches have shown that calcite filtration is a reliable remineralization method as no continuous chemical addition is required and calcite is inexpensive, readily available, safe to handle and easy to store (Shemer et al, 2013, Van Der Laan. H., 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonging the contact time of the feed water with the media is not an economically attractive option as the investment cost of the process would increase. Improved performance of the calcite beds by CO2 injection is mentioned in the literature [12,13]. However, for purpose of the domestic GW treatment, CO2 injection complicates the operation and maintenance of the process and would also add an additional cost.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the wealth of information on the effectiveness of implementing a calcite contactor to remineralize desalted RO permeates [12,13] and its ability to adsorb divalent metallic cations on its surface [14,15,16], to the best of our knowledge, removal of Mn and Fe from a soft water while simultaneously adjusting its hardness level (without dosing CO2) by means of a calcite contactor is not addressed in the scientific literature. In this perspective, the aim of this research is to design a simple and compact, yet robust hybrid HFNF–calcite contactor process for domestic treatment of GWs (containing a high level of Mn, Fe and NOM).…”
Section: Introductionmentioning
confidence: 99%
“…The basic rate equation [15,19,21] is described by the difference between the calcium solution concentration [Ca +2 ] and the equilibrium calcium concentration [Ca +2 ] e on the solution-calcite interface:…”
Section: Rate Equationsmentioning
confidence: 99%